Concept Analysis Patient Centred Care In Diabetes Mellitus With Heart Disease Complication - Pranata, Satriya; Aisah, Siti; Vranada, Aric; Taliki, Verawaty; Adriani, Sri; Riyanto, Ujang; Fariqoini, Ayul; Harmoko, Tri (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT PCC of patients with diabetes mellitus with heart disease is a patient-focused service with a holistic approach (bio-psychosocial-spiritual) to provide respectful and individualized care, enabling negotiation of care and offering choice through a therapeutic relationship where patients with diabetes mellitus with heart disease complications are empowered to be involved in health decisions at whatever level is desired by the individual receiving care. However, the application of this concept in services has not been comprehensively clarified. The purpose of this analysis is to describe and explain the concept of PCC in patients with diabetes mellitus with heart disease complications. Walker and Avant's concept analysis process was used to analyze the PCC concept. Six main defining attributes were identified: “ autonomy support; shared decision making; cooperation and collaboration; communication and education; emotional support, involvement of family and others. The predecessor analysis included several options with different possible outcomes, substantial patient-focused care conflicts, the need to recognize the health situation of patients with diabetes mellitus complicated by heart disease, and the willingness to participate in care. All of these factors are directly associated with different patient outcames and indirectly associated with outcames through patient activation. Kata Kunci: Patient Centred Care, Diabetes Mellitus, Heart Disease